FIRE-SAT un sistema satellitare per il monitoraggio sistematico, dinamico ed integrato degli incendi boschivi: la sperimentazione operativa nella regione Basilicata - Lanorte, Antonio; Lasaponara, Rosa (GEOmedia, 2013)
Il problema della gestione del fenomeno degli incendi boschivi è molto complesso, perché comprende una serie diaspetti connessi alle caratteristiche della vegetazione, alla morfologia del territorio, ai fattori meteorologici, ai fattoriantropici, etc. Risulta pertanto fondamentale e molto utile un approccio modellistico. I modelli matematici fornisconoun supporto essenziale nella valutazione dell'efficacia di possibili strategie di previsione e controllo del fuoco. Abstract FIRE_SAT project has been funded by the Civil Protectionof the Basilicata Region in order to set up alow cost methodology for fire danger monitoringand fire effect estimation based on satellite EarthObservation techniques.To this aim, NASA Moderate Resolution ImagingSpectroradiometer (MODIS), ASTER, Landsat TMdata were used. Novel data processing techniqueshave been developed by researchers of the ARGONLaboratory of the CNR-IMAA for the operativemonitoring of fire. In this paper we only focuson the danger estimation model which has beenfruitfully used since 2008 to 2012 as an reliable operativetool to support and optimize fire fightingstrategies from the alert to the management ofresources including fire attacks.The daily updating of fire danger is carried outusing satellite MODIS images selected for theirspectral capability and availability free of chargefrom NASA web site. This makes these data setsvery suitable for an effective systematic (daily) and sustainable low-cost monitoring of large areas.